2019
DOI: 10.4317/jced.56470
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution of complete-arch implant-supported prostheses reinforced with silica-nylon mesh

Abstract: Background: This study evaluated the presence of a silica-nylon mesh and two cantilever lengths on the biomechanical behavior of complete-arch implant-supported prostheses. Material and Methods: Twenty-four (24) complete mandibular arch implant-supported prostheses were divided into 4 groups according to the presence of reinforcing mesh (with or without) and the cantilever length (molar -15 mm or premolar -5 mm). The specimens were submitted to strain gauge analysis (30-kgf, 10 s) at different points (molar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…20,22 The finite element analysis in the present study was consistent with the findings reported in the literature once the stress concentration took place over the occlusal contacting surface and at the connector regions. 25,26 Additionally, previous studies reported that the presence of filler-reinforcement improved the stress distribution through the prostheses. 25 In the present study, the FEA results were consistent with the fracture analyses by FEGSEM.…”
Section: E6mentioning
confidence: 97%
See 1 more Smart Citation
“…20,22 The finite element analysis in the present study was consistent with the findings reported in the literature once the stress concentration took place over the occlusal contacting surface and at the connector regions. 25,26 Additionally, previous studies reported that the presence of filler-reinforcement improved the stress distribution through the prostheses. 25 In the present study, the FEA results were consistent with the fracture analyses by FEGSEM.…”
Section: E6mentioning
confidence: 97%
“…25,26 Additionally, previous studies reported that the presence of filler-reinforcement improved the stress distribution through the prostheses. 25 In the present study, the FEA results were consistent with the fracture analyses by FEGSEM. Regions of fractures were detected mainly in the transition region between pontics, at thin regions, and at the cantilever.…”
Section: E6mentioning
confidence: 97%
“…Next, previously modeled 22 morse taper internal connection implants (10 × 4.1 mm) were selected ( Fig. 1C ).…”
Section: Methodsmentioning
confidence: 99%
“…In order to avoid this problem, the addition of reinforcing materials to the main structure has been proposed, including metal beams, the incorporation of fibers and glass meshes, silica, carbon, polyamide, etc., [ 10 , 11 , 12 , 13 ]. One such reinforcing material is graphene, added to the composition of the PMMA discs in the form of small amounts of graphene particles.…”
Section: Introductionmentioning
confidence: 99%